Evolutionary dynamics of the immunodominant repeats of the Plasmodium vivax malaria-vaccine candidate circumsporozoite protein (CSP) - Patil, Aarti (2010)
The circumsporozoite protein (CSP) of Plasmodium vivax, a major target for malaria vaccine development, has immunodominant B-cell epitopes mapped to central nonapeptide repeat arrays. To determine whether rearrangements of repeat motifs during mitotic DNA replication of parasites create significant CSP diversity under conditions of low effective meiotic recombination rates, we examined csp alleles from sympatric P. vivax isolates systematically sampled from an area of low malaria endemicity in Brazil over a period of 14 months. Nine unique csp types, comprising six different nonapeptide repeats, were observed in 45 isolates analyzed. Identical or nearly identical repeats predominated in most arrays, consistent with their recent expansion. We found strong linkage disequilibrium at sites across the chromosome 8 segment flanking the csp locus, consistent with rare meiotic recombination in this region. We conclude that CSP repeat diversity may not be severely constrained by rare meiotic recombination in areas of low malaria endemicity. New repeat variants may be readily created by nonhomologous recombination even when meiotic recombination is rare, with potential implications for CSP-based vaccine development.